Muscle response to the association of statin and physical exercise in rats - Bonfim, Mariana Rotta; Jose Carlos Silva, Camargo Filho [UNESP]; Marques Vanderlei, Luiz Carlos; Trevizan Padulla, Susimary Aparecida; Accioly, Marilita Falangola; Silva Souza, Doroteia Rossi; Azoubel, Reinaldo (Soc Chilena Anatomia, 2009)
Physical exercise and statins, which are recommended for the treatment of dyslipidemia, are independently associated to the occurrence of muscle injury. The objective is analyze the effect of aerobic exercise associated to the use of simvastatin on the morphology of the gastrocnemius muscle. Thirty Wistar rats were divided into six groups, two of which received a standard diet (1 sedentary and 1 exercised) and four (1 sedentary with medication, 1 sedentary without medication, 1 exercised with medication, 1 exercised without medication) received a hypercholesterolemic diet (standard diet with the addition of cholesterol and coconut oil). Simvastatin (20 mg/Kg) was administered five days a week for eight weeks, together with aerobic training on a treadmill (9.75 m/min) for 60 minutes a day. The gastrocnemius muscle was removed, sliced, stained with Hematoxylin-Eosin and submitted to a histochemical reaction to determine mitochondrial activity. The data were analyzed using a paired t-test, analysis of variance and Scheffe's post hoc test (p<0.05). Greater histological alterations were found in the medicated and exercised animals, with a greater frequency of occurrence as well. The histochemical analysis revealed that the medicated groups had fibers with more intensive mitochondrial activity alongside fibers with an absence of reaction. The morphometric analysis revealed no significant differences between groups. It is suggested that simvastatin is a medication that leads to the occurrence of muscle injury and its administration in association with physical activity may exacerbate these injuries. This finding may be related to cellular respiration.

El ejercicio físico y las estatinas, son intervenciones recomendadas para el tratamiento de la dislipidemia y están independientemente asociadas con la ocurrencia de lesiones musculares. El objetivo fue analizar el efecto del ejercicio aeróbico asociado al uso de la sinvastatina en la morfología del músculo gastrocnemio. 30 ratas macho Wistar fueron divididos en 6 grupos, de los cuales 2 recibieron ración padrón, sedentarios, ejercitados y 4 recibieron dieta con alto nivel de colesterol, sedentarios con y sin medicamento, ejercitados con y sin medicamentos. La dieta fue elaborada a partir de una dieta padrón aumentada de colesterol y aceite de coco. La Sinvastatina (20 mg) fue administrada por 5 días por semana durante 8 semanas (20 mg/kg), junto al entrenamiento aeróbico en la estera (9,75 m/min) por 60 minutos por día. El músculo gastrocnemio colectado fue cortado y colorido por el método Hematoxilina-Eosina y sometido a una reacción histoquímica para verificar la actividad mitocondrial. Los datos fueron analizados utilizando el test t pareado, análisis de la variancia e Pos-Hoc de Scheffé, adoptándose p<0,05. Se verifico la presencia de alteraciones histológicas más significativas en los animales medicados y ejercitados, siendo también mayor la frecuencia de ocurrencia. El análisis histoquímica apunto que los grupos medicados presentaron fibras con actividad mitocondrial más intensa, al lado de fibras con pérdida de reacción. Los resultados de la morfometría no mostraron diferencias significativas entre los grupos estudiados. Se puede sugerir que la simvastatina es un medicamento que lleva a la ocurrencia de lesiones musculares e que su administración concomitante con la práctica de actividad física puede exacerbar estas lesiones, pudiendo tal hecho, estar relacionado con la respiración celular.
Respuestas musculares de la asociación de estatina y ejercicio físico aeróbico en ratas
Keywords: Hydroxymethylglutaryl-CoA Reductase Inhibitors; Exercise; Skeletal Muscle